A High-Efficiency Induction of Dopaminergic Cells from Human Umbilical Mesenchymal Stem Cells for the Treatment of Hemiparkinsonian Rats. Issue 11 (November 2015) - Ko, Tsui-Ling; Fu, Yu-Yi; Shin, Yang-Hsin; Lin, Yi-Hui; Ko, Miau-Hwa; Fu, Tz-Win; Lin, Tzu-Yung; Hsiao, Hsiao-Sheng; Chu, Pei-Ming; Fu, Yu-Show
The success rate in previous attempts at transforming human umbilical mesenchymal stem cells (HUMSCs) isolated from Wharton's jelly of the umbilical cord into dopaminergic cells was a mere 12.7%. The present study was therefore initiated to establish a more effective procedure for better yield of dopaminergic cells in such transformation for more effective HUMSC-based therapy for parkinsonism. To examine, in vitro, the effects of enhanced Nurr1 expression in HUMSCs on their differentiation, cells were processed through the three-stage differentiation protocol. The capacity of such cells to synthesize and release dopamine was measured by HPLC. The therapeutic effects of Nurr1-overexppressed HUMSCs were examined in 6-hydroxydopamine-lesioned rats by quantification of rotations in response to amphetamine. Enhanced Nurr1 expression in HUMSCs promoted the transformation into dopaminergic cells in vitro through stepwise culturing in sonic hedgehog, fibroblast growth factor-8, and neuron-conditioned medium. The success rate was about 71%, as determined by immunostaining for tyrosine hydroxylase and around 94 nM dopamine synthesis (intracellular and released into the culture medium), as measured by HPLC. Additionally, transplantation of such cells into the striatum of hemiparkinsonian rats resulted in improvement of their behavioral deficits, as indicated by amphetamine-evoked rotation scores. Viability of the transplanted cells lasted for at least 3 months as verified by positive staining for tyrosine hydroxylase. Nurr1, FGF8, Shh, and NCM can synergistically enhance the differentiation of HUMSCs into dopaminergic cells and may pave the way for HUMSC-based treatments for Parkinson's disease.